Policy Implementation of the Prosperous Rice Assistance Program : Research Study in Tukmudal Village Cirebon Regency - Adzhabibi Sentosa, Albi; Romlah, Siti; Abijaya, Sastra (Jurnal Polisci, 2023)
This study aimed to determine the implementation of the policy for the Prosperous Rice Assistance Program in Tukmudal Village, Sumber District, Cirebon Regency. This study uses qualitative methods and data collection processes by conducting interviews, documentation, and observation. The informant selection technique in this study used a purposive sampling technique. The results of the study are: (1) the communication carried out by the organizers, especially village administrators related to the prosperous rice assistance program, is carried out systematically using mobile phones as a communication medium. (2) the resources for implementing the Prosperous Rice Assistance Program are adequate, sufficient, and of good quality. (3) the disposition in the implementation of the Prosperous Rice Assistance Program is carried out under the regulations that have been determined by the sub-district (puskesos) conduct partnerships with the post office, where the post office acts as a significant delivery person to the sub-district and the sub-district as the leading distributor to the community. (4) the bureaucratic structure in implementing the Prosperous Rice Assistance program uses the structure of the social ministry because this program is directly from the center.